An Analysis on Pragmatic Force of Declarative Utterances Used by the Main Character in Mona Lisa Smile Movie and its Implication on Language Teaching - Juhariyah Nur Hakim (Journal of Pragmatics Research, 2019)
This research uses a descriptive qualitative method. The source of the data are document (the authentic manuscript) and video of “Mona Lisa Smile” film.  The goals of this research are (1) to identify the contexts of declarative utterances uttered by the main character (Katherine Wattson) in the film entitled “Mona Lisa Smile”, (2) to explain the pragmatic forces of declarative utterances. To find the pragmatic forces of declarative utterances in the film entitled “Mona Lisa Smile” the researcher identifies the context of each datum in declarative utterance based on Austin’s classification of act performance in language. There are 69 utterances in the film, then the researcher randomly takes 35 utterances of declarative utterances to be analyzed. The results of this research are, that (1) In every utterance, context has important role in determine the meaning of the utterance, (2) The hearer’s response to Katherine Watson’s declarative utterances varies. The hearer’s response can be in forms of a statement, question, act and sometimes silence to Katherine utterances, (3) From the 35 of declarative utterances that have been uttered by Katherine Watson there are 13 kinds of force: consisting of insisting, claiming, complaining, apologizing, requesting, appointing, ordering, warning, suggesting, blaming, sentencing, asking, and advising. The implications of this research on teaching and learning activity are, (1) the pragmatic force of declarative utterances can be used as teacher’s classroom instruction, and (2) the pragmatic force of declarative utterances can be used as a teaching material.  Keywords: pragmatic, speech act, illocution, declarative